2014
DOI: 10.1007/s12928-014-0287-z
|View full text |Cite
|
Sign up to set email alerts
|

Extensive arterial repair one year after paclitaxel-coated nitinol drug-eluting stent vs. bare-metal stent implantation in the superficial femoral artery

Abstract: Arterial repair differences between paclitaxel-coated nitinol drug-eluting stent (DES) vs. bare-metal stent (BMS) up to 1 year after implantation in the superficial femoral artery (SFA) have not been well characterized. We compared angioscopic findings 1 year after implantation in the SFA of 22 DES in 18 patients and 12 BMS in 9 patients (follow-up period 354 ± 49 vs. 383 ± 81 days, P = 0.20). Neointimal coverage (NIC) was graded as: 0, stent struts exposed; 1, struts bulged into the lumen, although covered; 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 22 publications
(37 reference statements)
0
4
1
Order By: Relevance
“…Previous angioscopic studies reported that yellow plaque was less frequently observed 12 months after implantation of a bare nitinol stent in femoropopliteal lesions than at 3 months. 11, 13 However, in the present study, the maximum yellow color grade was not significantly different among the 3 groups after FP-DES implantation. This may be attributed to the this study.…”
Section: Discussioncontrasting
confidence: 61%
See 2 more Smart Citations
“…Previous angioscopic studies reported that yellow plaque was less frequently observed 12 months after implantation of a bare nitinol stent in femoropopliteal lesions than at 3 months. 11, 13 However, in the present study, the maximum yellow color grade was not significantly different among the 3 groups after FP-DES implantation. This may be attributed to the this study.…”
Section: Discussioncontrasting
confidence: 61%
“…This result differs from the findings of a previous angioscopy report evaluating intravascular status 12 months after PF-DCS implantation. 13 In that study, the grade of dominant neointimal coverage 12 months after PF-DCS implantation was mostly Grade 3. 13 This difference could be explained by differences in the duration of paclitaxel elution.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…Previous studies have typically only reported thrombosis rates through 1 year. Angioscopic observations in Japan have reported some evidence of thrombus with possible incomplete endothelial coverage at 2 months, but adequate healing at 1 year [ 13 , 14 ]. Based on these observations, the continuation of dual antiplatelet therapy could be important to minimize the incidence of stent thrombosis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, recently, it has been reported that angioscopy, which was usually used for evaluation of coronary arterial healing following stenting, [1][2][3][4] could be applied to evaluate the characterization of inside the vessel during and after endovascular therapy (EVT) including stent implantation in the femoropopliteal lesions. [5][6][7] Angioscopy can directly visualize the grade in the femoropopliteal lesions. Therefore, we report 2 cases who showed direct visualization of effect of ELA for femoropopliteal ISR lesions using angioscopy.…”
Section: Introductionmentioning
confidence: 99%